Determining Factors in Choosing a Caesarean Section: The Role of Health Financing and Availability of Health Facilities in Indonesia - Alfiena Nisa Belladiena; Ayu Ashari; Nugraheni Kusumawati; Syifa Sofia Wibowo; Fitria Wulandari; Heru Pramono Hadi; Aries Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The rising global cesarean section (SC) rate, projected to reach 29% by 2030, is a concern in Indonesia, where SC prevalence increased to 25.9% in 2023 from 17.6% in 2018. While medical indications drive SC, non-clinical factors like financing and healthcare access may contribute to overuse. This study examines the role of Indonesia’s BPJS health insurance and hospital availability in determining SC utilization. A cross-sectional analysis was conducted using SKI 2023 data, including 70,916 women with deliveries between 2018 and 2023 (weighted n = 20,076,001). Bivariate associations were assessed using chi-square tests with complex sample design, applying survey weights for national representativeness. SC prevalence was 25.9%, with 34.9% of BPJS-covered deliveries being SC compared to 10.8% for out-of-pocket payments (p < 0.001). Hospital availability within the district was associated with a 27.0% SC rate versus 16.1% where no access existed (p < 0.001). Private insurance (50.3%) and employer-funded (37.4%) deliveries also showed higher SC rates. BPJS coverage and hospital availability significantly influence SC utilization in Indonesia, suggesting improved access but potential overuse. Rural disparities highlight the need for infrastructure investment to ensure equitable maternal care under Universal Health Coverage. Further research with causal methods is recommended.